Phosphate Ion Removal from Aqueous Solution Using an Iron Oxide-Coated Fly Ash Adsorbent - Shuhua Yao; Jinyan Li; Zhongliang Shi (Adsorption Science & Technology)
The ability of an iron oxide/fly ash composite adsorbent prepared with municipal solid waste fly ash and iron nitrate to remove phosphate ions from aqueous solutions has been tested. The characteristics and physicochemical performances of the composite were investigated via nitrogen adsorption and scanning electron microscopy (SEM) studies. The comparative adsorption of phosphate ions by the composite adsorbent and fly ash was investigated using batch experiments. It was found that the adsorption properties of the composite adsorbent towards phosphate ions depended on the pH value of the solution and the anion concentration in the same. The equilibrium data were analyzed using the Langmuir and Freundlich isotherms, from which it was shown that the adsorption capacities for phosphate ions at pH 3.0 were 27.39 mg/g for iron oxide/fly ash and 18.90 mg/g for fly ash. The results showed the adsorption patterns for phosphate ions with fly ash and iron oxide/fly ash composite adsorbent showed a better match to the Freundlich model rather than the Langmuir model. The adsorption kinetic data could be well described by the Lagergren pseudo-second-order kinetic equation. The effect of temperature on the adsorption phenomena was investigated, the results indicating that phosphate ion removal by iron oxide/fly ash composite adsorbent was endothermic in nature.